The Word Made Flesh and the Spirit’s Breath: Bridging Christology and Pneumatology in Animal Theology - Daniela Rizzo (Religions)
This paper proposes a synthesis of Christological and pneumatological insights to present a more inclusive vision of creation’s role in divine worship and redemption. While deep incarnation emphasizes Christ’s identification with all of creation, this study extends the discussion by incorporating the Spirit’s ongoing work through the framework of animal glossolalia. Nonhuman creatures are seen not merely as passive recipients of Christ’s redemptive work but as active participants in cosmic worship through the Spirit’s intercession. By uniting the shared flesh of Christ with the Spirit’s transformative presence, the paper suggests a more integrated theological vision that includes all living beings in the divine narrative. This approach invites us to reconsider the role of animals within a broader ecological and theological framework, urging a reimagining of their spiritual capacities and their place in the eschatological hope for the renewal of all creation.